2023
DOI: 10.3390/nano13182511
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cellulose Nanofibres on Dewatering during Wet-Forming and the Mechanical Properties of Thermoformed Specimens Made of Thermomechanical and Kraft Pulps

Eirik Ulsaker Jacobsen,
Simen Prang Følkner,
Jørgen Blindheim
et al.

Abstract: Due to environmental concerns regarding single-use plastic materials, major efforts are being made to develop new material concepts based on biodegradable and renewable resources, e.g., wood pulp. In this study, we assessed two types of wood pulp fibres, i.e., thermomechanical pulp (TMP) and Kraft pulp fibres, and tested the performance of the fibres in wet-moulding and thermopressing trials. Kraft pulp fibres appeared to retain more water than TMP, increasing the dewatering time during wet-moulding and appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…It can be concluded that organosolv fibers appeared particularly suited for pote thermoformed products that require resistance to we ing, e.g., trays for food packag Materials for food packaging usually include, e.g., fossil low-and high-den polyethylene (LDPE and HDPE). The strength and modulus of LDPE and HDPE roughly between 10 and 30 MPa and 0.3 and 1.0 GPa, respectively [5], which comparable to the mechanical properties obtained in this study (Figure 6). Although elongation of the thermopressed handsheets are considerably lower (<10%) than thos PE materials (>500%), this is not considered a major drawback, as a high stiffnes particularly considered crucial food packaging and trays [46].…”
Section: Water Interactionssupporting
confidence: 89%
See 2 more Smart Citations
“…It can be concluded that organosolv fibers appeared particularly suited for pote thermoformed products that require resistance to we ing, e.g., trays for food packag Materials for food packaging usually include, e.g., fossil low-and high-den polyethylene (LDPE and HDPE). The strength and modulus of LDPE and HDPE roughly between 10 and 30 MPa and 0.3 and 1.0 GPa, respectively [5], which comparable to the mechanical properties obtained in this study (Figure 6). Although elongation of the thermopressed handsheets are considerably lower (<10%) than thos PE materials (>500%), this is not considered a major drawback, as a high stiffnes particularly considered crucial food packaging and trays [46].…”
Section: Water Interactionssupporting
confidence: 89%
“…To compare the means of two individual measurements, the two-sided t-test was conducted according to Equations ( 4) and (5) given by Kalpic et al [37]. Here, the variable T was calculated from the sample means X i with standard deviation S i and sample size n i .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation